Implementasi Media Flipbook dalam Pembelajaran Menulis Teks Cerpen di Kelas XI SMA Negeri 16 Semarang - Neni Widyawati; Rifana Yuniartanti; Rochimmatussaadah Rochimmatussaadah; Fahrizal Lalang Sitoro; Asep Purwo Yudi Utomo; Isnarto Isnarto; Kurniawan Sutrisnadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article aims to describe the implementation of flipbook media in teaching short story writing in class XI SMA Negeri 16 Semarang. The problem in this study is that there is no use of instructional media to construct short story texts in class XI students. Therefore, researchers try to apply flipbook media, especially in learning to compose short story texts. The article that the researcher wrote is a conceptual article. Conceptual article contains ideas In this article data is obtained by direct observation in class. While writing this article is done by identifying and seeking information from relevant data, analyzing the results, then developing and conveying ideas based on the researcher's understanding. Learning outcomes are expected to be more optimal with the use of learning media that is not boring for students. The solution that can be used with these problems is the use of flipbook media. The use of flipbook learning media is expected to be able to overcome the difficulties experienced by students in learning to write short story texts and students are not easily bored in participating in learning.